PERCEIVED LEVEL OF CORRUPTION AMONG PUBLIC OFFICERS IN THE AGRICULTURAL SECTOR IN SOUTHWESTERN NIGERIA
Corruption constitutes a great challenge to effective agricultural policy implementation. Global ratings of countries' level of corruption have prompted conscious efforts in promoting transparency, particularly in Nigeria. However, there is dearth of information on corruption in organisational management practices in Nigeria's public sectors, including agriculture, which makes development of appropriate preventive measures difficult. Perceived level of corruption among public officers in the agricultural sector in southwestern Nigeria was therefore investigated. Multistage random sampling procedure was used to select officers who were involved in agricultural policy implementation and service delivery from the Agricultural Development Programme (ADP) and Ministry of Agriculture and Natural Resources (MANR) in Oyo, Ekiti and Osun states. Fifty percent of the ADP zones were selected in each sampled state out of which 10% of officers were randomly sampled, resulting in 37, 27 and 18 respondents for Oyo, Ekiti and Osun states respectively. From the MANR in each state, 10% of officers were sampled resulting in 39, 32 and 21 respondents for the states respectively. Structured questionnaire was used to collect information on personal characteristics, job satisfaction, attitude and perception of corruption, determinants of corruption and effectiveness of internal control measures. Indices of transparency in public service delivery, budget, personnel and procurement managements were generated and used to determine the perceived level of corruption. Data were analysed using descriptive statistics, composite indices, Chi square, t-test and ANOVA at p = 0.05. Most (77.6%) of the respondents were males and 87.4% had minimum of university education. Mean age and work experience were 40.4 ± 7.7 and 9.7 ± 8.2 years respectively. Majority of the respondents indicated a high level of job satisfaction (10.4 ± 1.5), had favourable attitude (18.2 ± 4.2) and perception (52.0 ± 5.2) of corruption. Majority (2.9 ± 1.0) had favourable attitude to influence peddling, patronage (2.3 ± 0.9), pork barreling (2.2 ± 1.0), private use of government resources (2.2 ± 1.1) and bureaucratic conflict of interests (2.0 ± 1.1). Effectiveness of internal control measures for corruption had low index of 14.9 ± 2.6. Major determinants of corruption among the public officers were greed (3.5 ± 0.7), poor working conditions (3.4 ± 0.7) and poor management system (3.1 ± 0.9). Transparency was high in personnel management (45.7 ± 6.1) but low in public service delivery (18.9 ± 3.8), budget (26.8 ± 4.5) and procurement managements (15.7 ± 3.6). Perceived level of corruption was high among 46.6% of the respondents. Mean corruption perception index was generally high (107.1 ± 8.1) but lower in MANR (106.3 ± 7.8) than in the ADP (108.0 ± 8.5). Significant relationship existed between respondents' sex and attitude to corruption (?2 = 11.3). No significant difference existed in the perceived level of corruption between the ADP and MANR and across the states. Perceived level of corruption in the agricultural sector of southwestern Nigeria was considerable. Public service delivery, procurement and budget management practices were avenues for corruption in the sector. Full compliance with regulations of organisational management practices would help reduce corruption.